(untitled) (Global Journal of Management and Business Research, 2016)
Macroeconomic variables indicate the overall situation of the country, which we expect to be more consistent, stable and grow over time. The unemployment rate in Bangladesh is 5% at 2012 which is lower than world unemployment (around 6%). Labor Force participation rate is also higher in Bangladesh (73.8% in 2000). On the other hand GDP growth rate even in 2008 was 6.6% where most of the countries had a negative growth rate in their GDP. In Bangladesh, more than 2% of GDP increase due to employment growth. The labor force was 49.5 million in 2006 which becomes 53.7 million in 2009 and now 54.1 million. The growth rate has been 2.7 percentage points a year. At the same time, GDP also increase at around 6% in last decade. In GDP, the share of agriculture sector is decreasing where other two major sectors industry and services are increasing and the same thing occurs in the case of employment. This study focuses on the parallel transformation of employment and GDP and its impact on our economy.